Ethnizität und Lokalität als Aufstiegsressourcen.: Theoretische Überlegungen und das Beispiel des Bildungsaufstiegs in der zweiten türkischen Migrantengeneration in Deutschland - Pott, Andreas (ERDKUNDE, 2004)
This article uses the recent upward mobility movements of parts of the second-generation labour immigrants in Germany as an opportunity to investigate the significance of ethnic and spatial differentiations in the context of social mobility. The way the interdisciplinary migration research deals with this topic up to now is highly inadequate. After the description of the conceptional basis of its limitations a different approach towards the interrelation of social mobility, ethnicity and space is suggested following the premises and theoretical decisions of systems theory. Within this theoretical framework the relevance of locality and ethnicity as useful mobility resources is discussed exemplarily analysing the mobility patterns of educationally successful Turkish climbers.